1996
DOI: 10.1126/science.271.5257.1858
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HIV-1 Replication in Lymphocytes by Mutants of the Rev Cofactor eIF-5A

Abstract: Eukaryotic initiation factor 5A(eIF-5A) is a cellular cofactor require d for the function of the human immunodeficiency virus type-1 (HIV-1) Rev trans-activator protein. The majority of a set of eIF-5A mutants did not support growth of yeast cells having an inactivated genomic copy of eIF-5A, indicating that the introduced mutation eliminated eIF-5A activity. Two nonfunctional mutants, eIF-5AM13 and eIF-5AM14, retained their binding capacity for the HIV-1 Rev response element:Rev complex. Both mutants were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
163
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 193 publications
(169 citation statements)
references
References 20 publications
5
163
0
1
Order By: Relevance
“…Additional effects of Rev are likely to occur at the level of facilitating viral RNA transport or translation. These transport effects could involve the specific interplay of other cellular factors, such as the nucleoporin-like Rab͞Rip proteins (49)(50)(51) or eIF 5A (52,53), with the leucine-rich activation domain of Rev (7), which functions as a nuclear export signal (54,55). Mutation of this leucine-rich domain results in the formation of potent dominant-negative inhibitors of Rev (56), which already have shown promise in early clinical trials (57).…”
Section: Discussionmentioning
confidence: 99%
“…Additional effects of Rev are likely to occur at the level of facilitating viral RNA transport or translation. These transport effects could involve the specific interplay of other cellular factors, such as the nucleoporin-like Rab͞Rip proteins (49)(50)(51) or eIF 5A (52,53), with the leucine-rich activation domain of Rev (7), which functions as a nuclear export signal (54,55). Mutation of this leucine-rich domain results in the formation of potent dominant-negative inhibitors of Rev (56), which already have shown promise in early clinical trials (57).…”
Section: Discussionmentioning
confidence: 99%
“…3G). According to previous data (33,45), these spots represent the unhypusinated (Fig. 3G, red arrow) and the more acidic unhypusinated and acetylated form of eIF-5A1 (Fig.…”
Section: Dhs Is Crucial For Embryonic Development As Well As For Viabmentioning
confidence: 99%
“…Rev's effector domain contains a leucine-rich nuclear export signal (NES), which binds the nuclear export receptor CRM1 (Weis 2002). Other cellular proteins have been shown to interact directly or indirectly with the Rev NES, including the kinesin-like Rev/Rex effector binding protein (REBP) and the eukaryotic initiation factor-5 alpha (eIF-5␣; Bevec et al 1996;Dayton 1996;Kjems and Askjaer 2000;Venkatesh et al 2003).…”
Section: Human Immunodeficiency Virus Rev Facilitates the Cytoplasmicmentioning
confidence: 99%
“…Rev's effector domain contains a leucine-rich nuclear export signal (NES), which binds the nuclear export receptor CRM1 (Weis 2002). Other cellular proteins have been shown to interact directly or indirectly with the Rev NES, including the kinesin-like Rev/Rex effector binding protein (REBP) and the eukaryotic initiation factor-5 alpha (eIF-5␣; Bevec et al 1996;Dayton 1996;Kjems and Askjaer 2000;Venkatesh et al 2003).The human Rev-interacting protein (hRIP), also known as hRab or Hrb, was identified using a yeast twohybrid screen with Rev as the bait (Bogerd et al 1995;Fritz et al 1995). Additional studies demonstrated a strong correlation between the ability of Rev NES mutants to support Rev function in yeast and their ability to interact with hRIP in the two-hybrid assay (Stutz et al 1996).…”
mentioning
confidence: 99%